On the temperature-dependence characterization and modeling of GaN HEMTs - Anwar Jarndal; Lutfi Albasha; Hasan Mir (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Thermal effects present a major challenge for all semiconductor devices, especially high-power transistors such as GaN High Electron Mobility Transistors (HEMTs). The combined internal and external temperatures significantly impact the device's small- and large-signal characteristics, leading to performance degradation. In this paper, a 10 × 200-µm GaN-on-Si substrate depletion-mode HEMT was characterized using DC (Direct Current) and pulsed IV measurement setups at different ambient temperatures and quiescent voltages. These measurements were used to investigate the influence of temperature on the drain current and to develop an electrothermal model for the device. The results show that the drain current is highly sensitive to temperature, exhibiting a significant reduction at higher temperatures, which in turn affects large-signal output power, gain, and power-added efficiency. Additionally, temperature has a stronger impact on parasitic resistances, indirectly affecting the DC and RF (Radio Frequency) characteristics of the device. This investigation highlights the critical role of thermal effects and underscores the need for effective thermal management strategies.